2004
DOI: 10.1073/pnas.0404057101
|View full text |Cite
|
Sign up to set email alerts
|

Fast folding of a helical protein initiated by the collision of unstructured chains

Abstract: To examine whether helix formation necessarily precedes chain collision, we have measured the folding of a fully helical coiled coil that has been specially engineered to have negligible intrinsic helical propensity but high overall stability. The folding rate approaches the diffusion-limited value and is much faster than possible if folding is contingent on precollision helix formation. Therefore, the collision of two unstructured chains is the initial step of the dominant kinetic pathway, whereas helicity ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…Kato et al (2010) studied the folding of mutants of S. nuclease, where NLIs were perturbed and concluded that the native NLIs established at the early stage of the folding process facilitate further secondary structure formation. Meisner and Sosnick (2004) studied the kinetics of folding of a two-chain engineered protein in which helicity and collision rate can be varied and concluded that an unstructured encounter complex can successfully initiate rapid folding, with helix formation occurring at a later stage. The collision-first route enables a high basal folding rate of any protein.…”
Section: Direct and Indirect Findings Consistent With The Closed Longmentioning
confidence: 99%
“…Kato et al (2010) studied the folding of mutants of S. nuclease, where NLIs were perturbed and concluded that the native NLIs established at the early stage of the folding process facilitate further secondary structure formation. Meisner and Sosnick (2004) studied the kinetics of folding of a two-chain engineered protein in which helicity and collision rate can be varied and concluded that an unstructured encounter complex can successfully initiate rapid folding, with helix formation occurring at a later stage. The collision-first route enables a high basal folding rate of any protein.…”
Section: Direct and Indirect Findings Consistent With The Closed Longmentioning
confidence: 99%
“…Along these lines, we have been interested particularly in coiled-coil ''trigger sequences,'' which encode stable monomeric ␣-helices that are indispensable for coiled-coil formation (14)(15)(16)(17)(18). Although there are a few examples of synthetic peptides that fold either into heterodimers (19) or at conditions of extremes of pH (20) without an apparent trigger sequence, the ''trigger site'' concept is generally accepted because these short autonomous helical folding units are structurally and functionally conserved in a large number of native coiled-coil proteins (reviewed in refs. [21][22][23][24].…”
mentioning
confidence: 99%
“…Indeed, a wealth of reports have been published on the folding of the yeast transcription factor GCN4-p1 (12,14,(17)(18)(19)(20)(21) with many reporting the protein to fold in a two-state mechanism. However, some have speculated about the existence of intermediates (22)(23)(24).…”
mentioning
confidence: 99%